ANALISIS KEMAMPUAN BERPIKIR KOMPUTASI MENGGUNAKAN SPEQ MATHEMATICS PADA SISWA SMP/TSANAWIYAH - Maulia Fadila; Yahfizham Yahfizham (CV. KAMPUS AKADEMIK PUBLISING, 2025)
The purpose of this study was to analyze the computational thinking skills of junior high school students in solving mathematics problems using the SpeQ Mathematics application. This study applies a qualitative approach with a descriptive design. Data were obtained through student journals and observations of student interactions with the application. The data analysis process was carried out using the Dedoose application to code and evaluate qualitative data based on computational thinking indicators, namely decomposition, pattern recognition, abstraction, and algorithms. The results of the analysis showed that the majority of students showed good abilities in terms of decomposition and pattern recognition, but faced challenges in the aspects of abstraction and algorithm construction. The use of the SpeQ Mathematics application has proven effective in helping students understand mathematical concepts with a more visual and interactive approach. Overall, this study concludes that the SpeQ Mathematics application can improve students' computational thinking skills, although additional practice is needed to develop abstraction and algorithm creation skills.